Fangchinoline inhibits the PEDV replication in intestinal epithelial cells via autophagic flux suppression - Zhang, Weixiao; Shen, Haiyan; Wang, Menglu; Fan, Xuelei; Wang, Songqi; Wuri, Nile; Zhang, Bin; He, Haiyan; Zhang, Chunhong; Liu, Zhicheng; Liao, Ming; Zhang, Jianfeng; et al. (Frontiers in Microbiology, 2023)
Animal and human health is severely threatened by coronaviruses. The enteropathogenic coronavirus, Porcine epidemic diarrhea virus (PEDV), is highly contagious, leading to porcine epidemic diarrhea (PED), which causes large economic losses in the world's swine industry. Piglets are not protected from emerging PEDV variants; therefore, new antiviral measures for PED control are urgently required. Herein, the anti-PEDV effects and potential mechanisms of fangchinoline (Fan) were investigated. Fan dose-dependently inhibited PEDV infection at 24 h post infection (EC50 value = 0.67μM). We found that Fan mainly affected the PEDV replication phase, but also inhibited PEDV at the attachment and internalization stages of the virus life cycle. Mechanistically, Fan blocked autophagic flux in PEDV-infected cells by regulating the expression of autophagy-related proteins and changing PEDV virus particles. In summary, Fan inhibits PEDV infection by blocking the autophagic flux in cells. Our findings will help to develop new strategies to prevent and treat PEDV infection.